Chipping away at public debt sources of failure and keys to success in fiscal adjustment - Mauro, Paolo (Wiley, 2011)
"This book, edited and researched by experts at the International Monetary Fund (IMF), looks at fiscal adjustment plans in advanced economies, comparing the planned or projected reductions in debts and deficits to the actual outcomes. It also looks at whether spending exceeded expectations or revenues fell short of expectations, and why, and whether planned debt reductions proceeded faster or slower than projected. The concluding chapters provide an overview of what conclusions can be drawn from the chapters in terms of lessons learned and how to have the best chance for successful fiscal adjustments"--